Effect of nanostructured TiO2 crystal phase on photoinduced apoptosis of breast cancer epithelial cells - Lagopati N (Dove Medical Press, 2014)
Nefeli Lagopati,1,2 Effie-Photini Tsilibary,1,* Polycarpos Falaras,2,* Panagiota Papazafiri,3 Evangelia A Pavlatou,4 Eleni Kotsopoulou,1 Paraskevi Kitsiou1,* 1Institute of Biosciences and Applications, 2Institute of Advanced Materials, Physicochemical Processes, Nanotechnology and Microsystems, National Center for Scientific Research “Demokritos”, Athens, Greece; 3Department of Animal and Human Physiology, Faculty of Biology, School of Science, National and Kapodistrian University of Athens, Athens, Greece; 4Laboratory of General Chemistry, School of Chemical Engineering, National Technical University of Athens, Athens, Greece *These authors contributed equally to this work Purpose: The use of nanoparticles has seen exponential growth in the area of health care, due to the unique physicochemical properties of nanomaterials that make them desirable for medical applications. The aim of this study was to examine the effects of crystal phase-nanostructured titanium dioxide particles on bioactivity/cytotoxicity in breast cancer epithelial cells. Materials and methods: Cultured Michigan Cancer Foundation (MCF)-7 and human breast adenocarcinoma (MDA-MB-468) breast cancer epithelial cells were exposed to ultraviolet A light (wavelength 350 nm) for 20 minutes in the presence of aqueous dispersions of two different nanostructured titanium dioxide (TiO2) crystal phases: anatase and an anatase–rutile mixture. Detailed characterization of each titanium dispersion was performed by dynamic light scattering. A 3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide (MTT) colorimetric assay was employed to estimate the percentage of viable cells after each treatment. Western blot analysis of protein expression and characterization, as well as a deoxyribonucleic acid (DNA)-laddering assay, were used to detect cell apoptosis. Results: Our results documented that 100% anatase TiO2 nanoparticles (110–130 nm) exhibited significantly higher cytotoxicity in the highly malignant MDA-MB-468 cancer cells than anatase–rutile mixtures (75%/25%) with the same size. On the contrary, MCF-7 cells (characterized by low invasive properties) were not considerably affected. Exposure of MDA-MB-468 cells to pure anatase nanoparticles or anatase–rutile mixtures for 48 hours resulted in increased proapoptotic Bax expression, caspase-mediated poly(adenosine diphosphate ribose) polymerase (PARP) cleavage, DNA fragmentation, and programmed cell death/apoptosis. Conclusion: The obtained results indicated that pure anatase TiO2 nanoparticles exhibit superior cytotoxic effects compared to anatase–rutile mixtures of the same size. The molecular mechanism of TiO2 nanoparticle cytotoxicity involved increased Bax expression and caspase-mediated PARP inactivation, thus resulting in DNA fragmentation and cell apoptosis. Keywords: nanostructured TiO2, anatase, rutile, photocatalysis, breast cancer epithelial cells, apoptosis